Dragon Fruit Peel Extract and Encapsulated Catfish Oil Formulation in Gummy Candy with Potential In Vitro Antihyperglycemia Properties - Aurelia, Jovita; Trifena, Felicia; Levi, Kelvin; Marcella, Maria; Septiyani; Agustinah, Widya (Journal Akademik Universitas Swiss German, 2022)
Red dragon (Hylocereus polyrhizus) fruit peel as household waste was still underutilized although it was high in bioactive compounds with antioxidant and antidiabetic properties. The oil extract of freshwater fish, such as catfish (Pangasius sp.) was high in monounsaturated fatty acids with reported antihyperglycemia properties. The objectives of this study were to encapsulate catfish oil extract, determine the most liked formulation of gummy candy with dragon fruit peel extract and encapsulated fish oil beads content, and analyze the proximate content and in vitro α-amylase inhibition activity of the most liked gummy candy formulation. The methods consisted of dragon fruit peel extraction, encapsulation of catfish oil extract using sodium alginate, gummy candy formulation, sensory evaluation, and analysis of color, proximate, and α-amylase inhibition activity. Twenty five percent w/w of the gummy candy ingredients were composed of the extracts and encapsulation beads at 1:1, 1:3, and 3:1 weight ratios. Encapsulation of the fish oil could mask the fishy odor in the gummy candy. All formulation could be molded into gummy candy perfectly and showed chewy texture. The addition of dragon fruit peel extract could increase the yellowness value, while the fish oil beads decreased the lightness value of the candy. The most liked gummy candy formulation was F3 (ratio 3:1). It was composed of 54.47% water, 1.59% db ash, 5.77% db fat, 1.82% db protein, 36.36% db carbohydrates and showed 46.49% α-amylase inhibition activity.